The Influence of Perceived Convenience and Service Features on Interest in Using the Dana Di Digital Wallet Application SETELUK DISTRICT KSB - Aprilia, Mila; Dianti, Ira; Al-gifari, Ma’ruf (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Many factors influence interest in using e-wallets on the DANA application, one of which is convenience and service features. The aim of this research is to determine the influence of perceived convenience and service features on interest in using the Dana Digital Wallet Application in Seteluk KSB District. The population in this research is the people of Seluk subdistrict, West Sumbawa regency. The data collection technique in this research uses a questionnaire. The data used is primary data and secondary data. In this research, the sample consisted of 100 respondents using a purposive sampling technique using the Slovin formula. The data analysis used in this research is quantitative using the multiple linear regression method. The data is processed using SPSS Statistics 25. The results show that simultaneously Perceived Convenience and Service Features have a significant effect on Interest in Using. Meanwhile, perceived ease of use partially has a significant positive effect on interest in using, while service features partially have a significant effect on interest in using. The large influence of perceived convenience and service features on interest in using is shown by the coefficient of determination of 703 (70.3%). These results show that the variables Perceived Ease (X1) and Service Features (X2) influence the variable Interest in Using (Y). Meanwhile, the remaining 29.7% was influenced by other factors not examined in this study.